Reaping what you sow : a comparative examination of torture reform in the United States, France, Argentina, and Israel - Carey, Henry F., 1953- (PSI reports (Westport, Conn.), 2012)
This book presents a cost-benefit analysis of torture, daring to ask if the use of torture is ever justified or always ill-advised. While the use of torture is variously presented either as an aberrant American weapon unleashed in the aftermath of the terror attacks of September 11 or as a necessary tool in the War on Terror, torture has a long history across cultures. Yet, the debate over the morality, and the legality, of the brutal practice flourishes. This volume presents a new angle in the study of this controversial practice, approaching the issue of torture from a cost-benefit analysis for the practicing nation, rather than from a sensationalist, emotive vantage point. Adopting a transnational approach, the author examines the use of torture by the French in Algeria, the Argentines within their own borders, the Israelis in the Middle East, and the Americans in Guantanamo and Abu Ghraib. In attempting to define torture, he asks: Is the information gained through torture worth the potential damage? What is the harm (or benefit) to the state once the torture becomes known? What are the political and strategic ramifications? Does torture help win wars? Can the use of torture bring about any lasting or beneficial reforms? These are daring questions seldom pondered. In asking them, this book will help to foster a discussion that is long overdue.